2009
DOI: 10.1007/s00383-009-2365-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Escherichia coli O157:H7 with necrotizing enterocolitis in a full-term infant

Abstract: Necrotizing enterocolitis (NEC) is the most common gastrointestinal emergency of the neonate. NEC is predominantly seen in premature infants; however, in rare instances it can affect full-term infants as well. Although the pathogenesis of NEC remains elusive, it is well established that bacterial colonization is required for development of this disease. In this report, we present a case of a full-term infant, who developed a very aggressive form of NEC and was found to have Escherichia coli (E. coli) O157:H7 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Recently NEC outbreaks have been linked with norovirus 1618 . Other studies have linked NEC with Clostridium perfringens 5 , Escherichia coli 6 , Clostridium difficile 4 , rotavirus 11 , astrovirus 9 and others. However, in almost all cases pathogen detection has been performed from stool samples but not from tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently NEC outbreaks have been linked with norovirus 1618 . Other studies have linked NEC with Clostridium perfringens 5 , Escherichia coli 6 , Clostridium difficile 4 , rotavirus 11 , astrovirus 9 and others. However, in almost all cases pathogen detection has been performed from stool samples but not from tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although considered an infectious disease for a long time, no single pathogen has been identified consistently. Reports of NEC have linked this disease with a variety of intestinal pathogens including Clostridium difficile 4 , Clostridium perfringens 5 , Escherichia coli 6 , adenovirus 7–8 , astrovirus 9 , enterovirus 10 , rotavirus 11 , and norovirus 12 . The number of reports of viral pathogens associated with NEC has tripled in the last 5 years and it has been suggested that rotavirus may constitute as much as 30% and norovirus 40% of NEC cases in single center cohorts 3,1112 .…”
Section: Introductionmentioning
confidence: 99%
“…We further characterized the genotypic variation of E. coli through reconstructing MLST loci-sequences from metagenomes 21 , and compared them to 25 recently characterized E. coli MLST genotypes associated with NEC 22,23 . Five E. coli genotypes were only observed in samples with high IP, two of which, sequence type 73 and 131, were previously identified as uropathogenic E. coli (UPEC) strains associated with NEC and infant mortality 23 ( Supplemental File 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, no specific microbe has been identified as determinant etiologic factor, and, rather surprisingly, the specific mechanisms by which infections contribute to NEC remain unknown. On the other hand, many pathogens may simulate a picture of NEC in neonates (Table 1) [7,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. The use of new molecular biology techniques has provided opportunities to reexamine this unresolved problem.…”
Section: Gut Microbiotamentioning
confidence: 99%